As Relações Étnico-Raciais Na Formação Inicial De Pedagogos - Reis, Natalia Do Carmo [UNIFESP] (2017)
The present research intends to investigate how the Pedagogy courses are formed pedagogues for the work with a reeducation of the ethnic-racial relations, as foreseen in the Resolution CNE / CP 01/2004. In addition to the documentary analysis of the Political Course Projects of the Universities (UNIFESP, UNICAMP, USP, UFSCAR and UNESP), the data collection materials were interviews with the coordinators of the Pedagogy courses of the five Universities, and with students of the last year of the course and Professores of two of them. Focal groups were used with the students. The objectives of the research are: to analyze the Political Projects of Course and the curricular proposals of the courses of Pedagogy with respect to the initial formation for the Reeducation of the Ethnic-Racial Relations; to analyze the perception that the undergraduate students of the Pedagogy course present about their formation with regard to the theme; to investigate the perception that teachers and coordinators of Pedagogy courses present about the training offered to students. The empirical data were analyzed in the light of the theoretical reference of Cavalleiro, Munanga, Silva, Gomes, Gramsci, Libâneo, Pimenta, among others. The study points out that, although Pedagogy courses are not providing students with subsidies to work with the reeducation of ethnic-racial relations, as foreseen in Resolution CNE/CP 01/2004, students are aware of the need to approach the theme both in Pedagogy courses and in everyday school life.